Assessing The Effectiveness of Biological, Chemical and Physics Treatment for Reducing Formalin in Sea Water - Mutia Nur Hayati; Diana Arfiati; Bagyo Yanuwiadi (Graduate Program, 2019)
Formalin is frequently found in water that has been used for the cultivation of grouper fish. If it enters public waters, the leftover water is feared to disturb organisms living in it. The objective of this research is to reduce formalin concentration in sea water through five treatment and control (no treatment), which is aeration, UV light from 10-watt light bulb, 3 g l-1 addition of active charcoal from corncob, 3 g l-1 addition of yeast, 10 ml l-1 addition of bacterial community. The formalin concentration was observed every 24 hours using formalin test kit for four days (4x24 hours). The results are that bacterial community treatment reduces formalin concentration to 0 mg l-1 after 48 hours, yeast treatment reduces the concentration to 0 mg l-1 after 96 hours, aeration reduces the concentration to 5 mg l-1 after 72 hours yet bouncing back up after 96 hours. Control, UV treatment, and active charcoal treatment are similar in that those three treatments do not reduce the formalin concentration, remaining at 10 mg l-1. Therefore, addition of bacterial community can reduce formalin until 0 mg l-1 concentration in two days, and yeast addition can reduce it until 0 mg l-1 in four days. Hence, further researches about dissipating formalin in sea water using bacterial community with different dosage and time length are required.